1996
DOI: 10.1111/j.1530-0277.1996.tb01695.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Organ‐Specific Endpoints of Alcoholism

Abstract: Medical records of the 15,924 twin-pairs in the National Academy of Sciences-National Research Council (NAS-NRC) twin registry were collected for an additional 16 years through 1994 when the surviving twins were aged 67 to 77 years. Compared with earlier analyses (Hrubec, Z, and Omenn, G. S., Alcohol. Clin. Exp. Res., 5:207-215, 1981), when subjects were aged 51 to 61, there were 23% more diagnoses of alcoholism (34.4 per 1,000 prevalence), 32% more diagnoses of alcoholic psychosis (5.4 per 1,000), and 25% mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 14 publications
4
100
0
7
Order By: Relevance
“…6 Given the tight relationship between liver fi brosis/cirrhosis and alcohol consumption, 19 it may seem counterintuitive that alcohol-dependent patients without liver disease drink more than patients with alcoholrelated cirrhosis. However, genetic cofactors mean that only about 20-30% of lifelong alcoholics develop liver fi brosis and cirrhosis, 20,21 and the very heavy drinkers in these studies escape cirrhosis by virtue of their genes rather than their lifestyle. About 80% of the deaths directly attributable to liver disease are from ALD, 3,22 and a further 10% result from alcohol dependency, so the drinking behaviours of these two groups are absolutely critical to the accurate modelling of fi scal policies, including MUP.…”
Section: Discussionmentioning
confidence: 99%
“…6 Given the tight relationship between liver fi brosis/cirrhosis and alcohol consumption, 19 it may seem counterintuitive that alcohol-dependent patients without liver disease drink more than patients with alcoholrelated cirrhosis. However, genetic cofactors mean that only about 20-30% of lifelong alcoholics develop liver fi brosis and cirrhosis, 20,21 and the very heavy drinkers in these studies escape cirrhosis by virtue of their genes rather than their lifestyle. About 80% of the deaths directly attributable to liver disease are from ALD, 3,22 and a further 10% result from alcohol dependency, so the drinking behaviours of these two groups are absolutely critical to the accurate modelling of fi scal policies, including MUP.…”
Section: Discussionmentioning
confidence: 99%
“…The role of environmental factors that affect disease progression such as drinking habits and comorbidities has been known for many years [3] . However, twin studies, the enhanced sensitivity of female drinkers and the fact that only a minority of patients progress to cirrhosis despite heavy drinking clearly suggest a genetic pre-disposition [4,5] . Recent studies in multiethnic populations with nonalcoholic fatty liver disease (NAFLD) and ALD have demonstrated that the single-nucleotide polymorphism, the rs738409 variant, that encodes for an isoleucine to methionine substitution at position 148 (I148M) in the patatin-like phospholipase-3 (PNPLA3/Adiponutrin) gene is a strong disease modifier by influencing steatosis, liver enzymes and fibrosis progression [6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the involvement of genetics in the progression of alcoholic fatty liver to advanced ALD comes from a twin study that found the concordance rate of alcoholic cirrhosis to be significantly higher in monozygotic twins compared with dizygotic twins (16.9% vs. 5.3%, respectively). 34 Study of genes involved with alcohol metabolism (e.g., the alcohol and aldehyde dehydrogenases and cytochrome P450 2E1), as well as genes involved with inflammation (e.g., tumor necrosis factor ␣ and interleukin-10), have been inconclusive, with several allelic associations detected but not verified in follow-up studies. 29 Perhaps the most compelling genetic finding for advanced ALD risk involves the immune regulatory cytotoxic T lymphocyte antigen-4 gene, in which homozygosity for the A49G polymorphism was found to confer a significant risk of alcoholic cirrhosis (OR 3.5; P ϭ .03) in Italians.…”
Section: Paradigms Of Common Complex Liver Diseasesmentioning
confidence: 99%